2021
DOI: 10.3390/nu13020290
|View full text |Cite
|
Sign up to set email alerts
|

Stunting Malnutrition Associated with Severe Tooth Decay in Cambodian Toddlers

Abstract: Background: The persistently high prevalence of undernutrition in Cambodia, in particular stunting or chronic malnutrition, calls for innovative investigation into the risk factors that affect children’s growth during critical phases of development. Methods: Secondary data analysis was performed on a subgroup of children who were present at two time points within the Cambodian Health and Nutrition Monitoring Study (CAHENMS) and who were less than 24 months of age at the nominated baseline. Data consisted of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 56 publications
0
30
0
3
Order By: Relevance
“…The pooled proportion of caries among the 11 included studies in the total sample of 11,115 individuals was 38.7% (95% CI = 28.4% to 49.5%) (Q = 1277.61; DF = 10; p < 0.0001; I 2 = 99.22%; Egger’s test = 3.83; Kendall’s Tau = 0.09) ( Figure 2 ). The studies were conducted across six different LMICs, including Brazil [ 38 , 39 , 40 , 41 , 42 ], Nigeria [ 43 , 44 ], Cambodia [ 45 ], Tanzania [ 46 ], Mexico [ 47 ], and Ethiopia [ 48 ]. All the studies used either the dmft (decayed, missing, and filled primary teeth) or DMFT (decayed, missing, and filled permanent teeth) index, except for Pérez et al [ 47 ], who used the International Caries Detection and Assessment System II (ICDAS II) 1–6 index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled proportion of caries among the 11 included studies in the total sample of 11,115 individuals was 38.7% (95% CI = 28.4% to 49.5%) (Q = 1277.61; DF = 10; p < 0.0001; I 2 = 99.22%; Egger’s test = 3.83; Kendall’s Tau = 0.09) ( Figure 2 ). The studies were conducted across six different LMICs, including Brazil [ 38 , 39 , 40 , 41 , 42 ], Nigeria [ 43 , 44 ], Cambodia [ 45 ], Tanzania [ 46 ], Mexico [ 47 ], and Ethiopia [ 48 ]. All the studies used either the dmft (decayed, missing, and filled primary teeth) or DMFT (decayed, missing, and filled permanent teeth) index, except for Pérez et al [ 47 ], who used the International Caries Detection and Assessment System II (ICDAS II) 1–6 index.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies used either the dmft (decayed, missing, and filled primary teeth) or DMFT (decayed, missing, and filled permanent teeth) index, except for Pérez et al [ 47 ], who used the International Caries Detection and Assessment System II (ICDAS II) 1–6 index. The primary objective of the six studies [ 39 , 41 , 42 , 46 , 47 , 48 ] was to assess the contributing factors of dental caries, whereas five studies evaluated them as secondary objectives [ 38 , 40 , 43 , 44 , 45 ]. Four studies reported cross-sectional data of prospective cohorts, including birth cohorts, followed for three years [ 40 ] and twelve years [ 38 ], respectively, and childhood cohorts followed for one year each [ 41 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Severe early childhood caries (S-ECC) is highly prevalent globally and pose serious consequences for the child's quality of life. [1][2][3] The consequences of untreated S-ECC include multiple episodes of dental pain and infections, poor mastication, delayed physical growth and development, hypoplasia of developing permanent teeth, loss of school days, hampered learning, and compromised self-esteem. [1][2][3][4][5] Also, a child with ECC is more likely to suffer 10% increased odds of undernutrition with each deep carious tooth.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The consequences of untreated S-ECC include multiple episodes of dental pain and infections, poor mastication, delayed physical growth and development, hypoplasia of developing permanent teeth, loss of school days, hampered learning, and compromised self-esteem. [1][2][3][4][5] Also, a child with ECC is more likely to suffer 10% increased odds of undernutrition with each deep carious tooth. [6] Treatment of S-ECC is complex, expensive, and due to high caries risk relapses after treatments are common in children managed for S-ECC.…”
Section: Introductionmentioning
confidence: 99%
“…Renggli et al [ 18 ] further analyzed data of the Cambodian Health and Nutrition Monitoring Study (CAHENMS) on sociodemographic characteristics, feeding practices and clinical measures for the anthropometric measures and dental status of related Cambodian toddlers. Based on the results, they concluded that severe caries experience was associated with poorer childhood growth and, as such, could be an underinvestigated contributor to stunting.…”
mentioning
confidence: 99%